Breaking cycles of violence, one wave at a time : a formative evaluation of the Waves for Change Surf Therapy programme - Snelling, Matthew (Institute for Monitoring and Evaluation, 2016)
This dissertation was a formative evaluation of the Waves for Change Surf Therapy Programme, and included both a process evaluation and an outcome evaluation. Waves for Change used surfing as a means of engaging children and adolescents thought to be at risk of long-term social exclusion. This engagement was necessary in order to deliver a psychosocial curriculum. Waves for Change aimed to use this curriculum to enhance psychosocial wellbeing and reduce antisocial behaviour, and association with antisocial peers. Five evaluation questions were generated using programme documents and a rapid evidence assessment. These were concerned with whether the programme was capable of enhancing psychosocial wellbeing, and reducing antisocial behaviour and association with antisocial peers. Further, the evaluation wished to determine whether the programme was correctly targeted, and delivered with fidelity. An intention to treat analysis was conducted within a randomised control trial, using 115 primary school students from Masiphumelele, Khayelitsha, and Lavender Hill. Further 88 interviews were conducted with programme beneficiaries, and 15 coaches were submitted to performance review. The programme was found to be suitably targeted, but delivery of the programme was not achieved with fidelity to the programme design. There were a number of reasons for this, including inadequate completion of programme tasks by coaches, and inadequate attendance by children and adolescents. The result was that children and adolescents received less than half of the psychosocial curriculum, and did not show a change on the outcomes of interest. However, this evaluation suggested that the programme is feasible, pending improvements.